Tanggung Jawab Perusahaan, Pariw PERAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN - Septiyaningsih, Nurul; Bambang Suharto (Tourism Department, State Polytechnic of Banyuwangi, 2024)
The tourism industry is a dynamic economic sector, contributing significantly to the global economy, including in Indonesia. Although it provides economic benefits such as job creation and increased state revenues, negative impacts on the environment and local communities are also found. The concept of sustainable tourism and corporate social responsibility (CSR) practices are in focus to mitigate these impacts. The Melati Bintan Resort case study demonstrates the successful implementation of CSR, focusing on cultural preservation, environmental protection, and community development. The systematic literature review (SLR) method was used to explore the latest trends and practices of CSR in the tourism industry. The results show that CSR can enhance a company's image and attract travelers who care about sustainability. Through the integration of CSR in its operations, Melati Bintan Resort creates positive sustainable impacts, although there is still room for improvement and innovation in achieving broader and more impactful sustainability.